Pengembangan Bahan Ajar Komik Berbasis Cerita Rakyat Bengkulu di SD - Muktadir, Abdul; Darmansyah, Ady (Jurnal PGSD, 2021)
The purpose of this study was to develop folklore-based comics teaching materials in Bengkulu City elementary schools. The method used is Research and Development using the ADDIE (Analysis–Design–Develop-Implement–Evaluate) model. However, this research is only in the Analysis-Design-Develop stage. Research data from interviews and questionnaires, interview data sources, observations, and documentation. The research instrument for analyzing the needs of teachers and students is in the form of a list of questions and questionnaires, descriptive data analysis. The results of the study were folklore-based comics in elementary schools in Bengkulu City. Folklore material is taught only at the competency stage. The competence of teachers regarding folklore is not sufficient, meaning that one story has not been fully understood, the number of stories known by the teacher does not exceed five stories.